PERBANDINGAN KINERJA METODE WARD DAN K-MEANS DALAM MENENTUKAN CLUSTER DATA MAHASISWA PEMOHON BEASISWA (STUDI KASUS : STMIK PRINGSEWU) - Satria, Fiqih; Aziz, R Z Abdul (244-5567)
This research aims to determine the steps cluster analysis method with Ward method and K-Means method, and compare the results of the analysis of the two methods for clustering student data related decision-making to determine the students are eligible to receive a Peningkatan PrestasiAkademik (PPA) scholarship and Bantuan Biaya Akademik (BBA) scholarship in STMIK Pringsewu. Cluster analysis was performed using IBM SPSS Version 23. Cluster Analysis results of both methods were compared using standard deviation ratio in the group (Sw) and the standard deviation between groups (Sb). Based on this research the ratio of the value of the standard deviation in the cluster and standard deviation between the cluster shows that the method of Ward and K-Means has the same performance when used in clustering scholarship PPA, both methods have a ratio value (Sw/Sb) are the same, 0.749959584 %. Therefore the results of the cluster that will be used as a reference in determining scholarship recipients PPA is the result of cluster analysis using Ward method or K-Means as they both have the results and performance of the same cluster. While on scholarship BBA clustering,Ward method has better performance than the KMeans method because the method of Ward have value of the ratio (Sw / Sb) 0.5346668% smaller than the value of the ratio (Sw/Sb) K-Means method 0.831525302 %. Therefore, the results of the cluster that can be used as a reference in determining BBA scholarship recipients is the result of cluster analysis using Ward method.Keywords: Cluster, K-Means, Scholarship, Standard Deviation, Ward.